2011
DOI: 10.1007/s00030-011-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

On the global wellposedness for the nonlinear Schrödinger equations with L p -large initial data

Abstract: Abstract. We consider the Cauchy problem for the nonlinear Schrödinger equations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…They split φ into the sum of a large L 2 function φ N and a small remainder function ψ N to obtain global solution of (C). In [6,7], we considered nonlinear Schrödinger equations with pure power nonlinearity |u| α−1 u in general space dimensions and obtained similar global existence results for a class of data which is not included in L 2 , and as a corollary we constructed global solutions for L p data p < 2 when α < α 0 where α 0 < 1 + 4/n is some power. One aim of the present paper is to establish a global solution of the Cauchy problem (H) with any mass subcritical nonlinearity (i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…They split φ into the sum of a large L 2 function φ N and a small remainder function ψ N to obtain global solution of (C). In [6,7], we considered nonlinear Schrödinger equations with pure power nonlinearity |u| α−1 u in general space dimensions and obtained similar global existence results for a class of data which is not included in L 2 , and as a corollary we constructed global solutions for L p data p < 2 when α < α 0 where α 0 < 1 + 4/n is some power. One aim of the present paper is to establish a global solution of the Cauchy problem (H) with any mass subcritical nonlinearity (i.e.…”
Section: Introduction and Main Resultsmentioning
confidence: 81%
“…We consider two solutions of (H). One is a global solution which is constructed by means of the splitting argument similar to the ones in [6,7,10] but we establish the solution in different function spaces based on the generalized Strichartz estimates, which is more suitable in the L p -framework. The other is a local solution based on [4,5] which is defined on some finite interval I and satisfies (1.2).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, in [20], Vargas and Vega studied the 1D cubic case and by means of a splitting argument, they showed that if φ / ∈ L 2 but φ is sufficiently close to an L 2 -function in some sense, then a global solution can be established. Later in [14], [15], [16] we considered the case of more general power α and use their approach to construct a global solution for L p -Cauchy data if p < 2 is sufficiently close to 2. This is based on the natural idea that any L p -function is "close" to an L 2 -function if p is near 2.…”
Section: Introductionmentioning
confidence: 99%